Antimetabolic Effects of Polyphenols in Breast Cancer Cells: Focus on Glucose Uptake and Metabolism - Keating, Elisa; Martel, Fátima (Frontiers in Nutrition, 2018)
In the last years, metabolic reprogramming became a new key hallmark of tumor cells. One of its components is a deviant energetic metabolism, known as Warburg effect—an aerobic lactatogenesis—characterized by elevated rates of glucose uptake and consumption with high-lactate production even in the presence of oxygen. Because many cancer cells display a greater sensitivity to glucose deprivation-induced cytotoxicity than normal cells, inhibitors of glucose cellular uptake (facilitative glucose transporter 1 inhibitors) and oxidative metabolism (glycolysis inhibitors) are potential therapeutic targets in cancer treatment. Polyphenols, abundantly contained in fruits and vegetables, are dietary components with an established protective role against cancer. Several molecular mechanisms are involved in the anticancer effect of polyphenols, including effects on apoptosis, cell cycle regulation, plasma membrane receptors, signaling pathways, and epigenetic mechanisms. Additionally, inhibition of glucose cellular uptake and metabolism in cancer cell lines has been described for several polyphenols, and this effect was shown to be associated with their anticarcinogenic effect. This work will review data showing an antimetabolic effect of polyphenols and its involvement in the chemopreventive/chemotherapeutic potential of these dietary compounds, in relation to breast cancer.